Thromboaspiration of a left-sided bioprosthetic valve thrombosis by a mini-access: the Lausanne novel procedure - Gunga, Ziyad; Rubimbura, Vladimir; Oberson, Denise; Monney, Pierre; Bechtold, Xavier; Ltaief, Zied; Rancati, Valentina; Eeckhout, Eric; Kirsch, Matthias (Frontiers in Cardiovascular Medicine, 2024)
Left-sided bioprosthesis valve thrombosis (LSBVT) is a challenging complication necessitating invasive interventions. In this study, we introduce a novel, minimally invasive approach. We used a cerebral embolic protection system and an Occlutech cannula connected to an extracorporeal circuit, providing safer thrombus aspiration compared to the AngioVac system. This technique offers a promising alternative for high-risk patients with LSBVT.